Analytical investigation of reinforced concrete frames under middle column removal scenario. Issue 9 (July 2018) - Mohajeri Nav, Foad; Usefi, Nima; Abbasnia, Reza
A simplified theoretical model is developed in the present study in order to predict the general behavior and resistance of reinforced concrete frames under column removal scenarios. The proposed model defines the load–deflection response of the middle joint above the removed column based on a four-stage procedure: classical beam mechanism stage, arching stage, transient stage, and catenary stage. A comprehensive evaluation study using two validation approaches is performed in order to investigate the reliability of the introduced model. For validation of theoretical model, the results of a comprehensive finite element method and experimental data were utilized and the results were compared with the theoretical model. The results demonstrated that the proposed theoretical procedure can establish a reliable foundation for progressive collapse assessment of reinforced concrete frame structures. The proposed model can also predict behavior of symmetrical frames, and this was validated by good agreement between finite element results and the results of the proposed numerical model.